INVESTIGATION OF IMMUNOSUPPRESSED PATIENTS FOR THE PRESENCE OF EBV DNA IN REAL TIME PCR - Tsvetelina Kostadinova; Liliya Ivanova; Zhivka Stoykova; Tatina Todorova; Liana Gercheva; Dobromir Staykov; Denitsa Tsaneva (Peytchinski Publishing, 2018)
Epstein-Barr virus (EBV) reactivates during immunosuppression (IS) and immune deficiency. The introduction of stem cell transplantation and the development of transplantology require compliance with criteria for assessing the risk of reactivation of latent viral infections, including EBV. There are no published EBVDNA findings in Bulgaria for such patient groups, Aim: The aim of this study is to assess the possible benefit of EBV PCR testing in immunosuppressed individuals. Materials and Methods: We investigated 50 immunosuppressed patients - 28 with various haematological diseases, 17 after kidney transplantationand5 patients with autologous stem cell transplantation (HSCT). Patients were first tested in an indirect ELISA to detect anti-VCA IgM/IgG (Euroimmun, Luebeck, Germany) and then in quantitative PCR (Sacace Biotechnologies S.r.l., Como, Italy). Results: We found ЕВV DNAin 14.0% (95% CI:5.8% - 26.7%, n=7) of all tested patients. The Real-time PCR results were in the range 100-500 copies/ml at the lower limit of the 500 copies/ml test positivity. The highest is the proportion of patients with haematological diseases (21.4%), predominantly with AML. Conclusion: We found a relatively small proportion of IS patients with detectable EBV DNA. For HSC-transplanted patients, we anticipate probable reactivation or reinfection in one patient, who was anti-VCA IgG positive in the primary study.